Risk factors associated with pulmonary exacerbations in pediatric patients with cystic fibrosis - Lubovich, S; Zaragoza, S; Rodríguez, V; Buendía, J; Vargas, BC; Moreira, JA; Galanternik, L; Ratto, P; Teper, A (Sociedad Argentina de Pediatria, 2019)
Introduction. Cystic fibrosis patients develop pulmonary exacerbations (PEs) that require intravenous treatment. The objective of this study was to determine the risk factors associated with PEs and establish the percentage of patients who failed to recover their lung function.